Handbook of forensic science - Fraser, Jim; Williams, Robin, 1946- (Willan Publishing ; Routledge, 2013)
Forensic science has become increasingly important within contemporary criminal justice, from criminal investigation through to courtroom deliberations, and an increasing number of agencies and individuals are having to engage with its contribution to contemporary justice. This Handbook aims to provide an authoritative map of the landscape of forensic science within the criminal justice system of the UK. It sets out the essential features of the subject, covering the disciplinary, technological, organizational and legislative resources that are brought together to make up contemporary forensic science practice. It is the first full-length publication which reviews forensic science in a wider political, economic, social, technological and legal context, identifying emerging themes on the current status and potential future of forensic science as part of the criminal justice system. With contributions from many of the leading authorities in the field it will be essential reading for both students and practitioners.